2008
DOI: 10.1007/s12306-007-0025-0
|View full text |Cite
|
Sign up to set email alerts
|

Vancomycin and meropenem in acrylic cement: elution kinetics of in vitro bactericidal action

Abstract: The Authors present a paper with a dual goal: in vitro evaluation of the elution of vancomycin and monitoring of its bactericidal action when the antibiotic is used in acrylic cement. Discs of cement with different concentrations of vancomycin alone or combined with meropenem were prepared. To assess the elution of vancomycin the discs were kept in physiological solution and periodically sampled for five weeks. The bactericidal action was assessed by putting the antibiotic discs in contact with colonies of Sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 14 publications
3
23
0
Order By: Relevance
“…Similar release profiles have been reported showing less than 5% of vancomycin was released from bone cement after 4-5 weeks in vitro [4,7]. The inclusion of sodium chloride in bone cement beads loaded with 2.5% vancomycin resulted in a concentration-dependent increase in the release rate of drug.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Similar release profiles have been reported showing less than 5% of vancomycin was released from bone cement after 4-5 weeks in vitro [4,7]. The inclusion of sodium chloride in bone cement beads loaded with 2.5% vancomycin resulted in a concentration-dependent increase in the release rate of drug.…”
Section: Resultssupporting
confidence: 84%
“…PMMA sets to a hard material that is impervious to water so that all drugs, studied to date, release very slowly from bone cement. Typically, less than 10% of the loaded drug is released after 6 weeks in aqueous environments [4,7,17,42,43]. Furthermore, most of the drug is eluted from the implant in the first week so that subsequent drug release levels may fall below the MIC with the added problem of the development of drug resistance.…”
Section: Introductionmentioning
confidence: 99%
“…PMMA is particularly interesting for this application as it is used extensively in orthopedic settings as a drug delivery vehicle for antibiotics because of its high biocompatibility and ease of manipulation . PMMA is a hydrophobic polymer; therefore, only a small percentage of the encapsulated drug is released from monolithic forms with low surface area to volume ratios . The release profiles may be modulated by the inclusion of water‐soluble excipients or increasing the surface area by using electrospinning .…”
Section: Resultsmentioning
confidence: 99%
“…The authors observed a 28-day elution rate that was remarkably higher than those reported by a previous study that evaluated vancomycin and meropenem after a similar observation time. 23 However, note that any comparison of their results with previous studies is difficult because of some methodological differences. Indeed, different factors, such as the cement characteristics, contact/exchange surface, compound conditions, and antibiotic type and amount, have been previously thought to determine the antibiotic release from the acrylic cement.…”
Section: Discussionmentioning
confidence: 99%